The Prevalence of Occupational Risk Factors and Occupational Diseases in Kerman, Iran - Maysam Rezapour; Zahra Khorrami; Raheleh Tabe; Narges Khanjani (Shahrekord University of Medical Sciences, 2019)
Background and aims: Many workers face significant hazardous workplace exposures, especially in developing countries. The objective of this study was to investigate the prevalence of occupational risk factors and common occupational diseases in Kerman. Methods: This study was based on data from occupational risk factor and disease monitoring systems available at Kerman Province Health Center during 2011-2015. These data are gathered semiannually by occupational hygienists based on standard checklists provided by the Ministry of Health and Medical Education and these checklists include exposures and diseases related to the workplace. Results: Based on the results, 292 (3.7%), 281 (3.58%), 261 (3.32%), and 115 (1.47%) cases were found regarding occupational hearing loss, respiratory conditions, work-related back pain, and musculoskeletal disorders, respectively, which were related to different occupational exposures diagnosed in Kerman during 2011-2015. Moreover, dust, work tools, wrong body position during work, and noise were the most common risk factors in this respect. Conclusion: Overall, occupational hazards are considered as an important health issue in Kerman. Therefore, it is necessary to control exposure to these risk factors in order to prevent occupational diseases.